A QoS-Based Topology Control Algorithm for Underwater Wireless Sensor Networks. (1st November 2010) - Liu, Linfeng
Abstract : The topology control techniques of underwater wireless sensor networks and terrestrial wireless sensor networks are significantly different because of the particularity of underwater environments and acoustic communication. In this paper, an underwater wireless sensor network model was constructed, and six universal topology control objectives were concluded. The QoS topology control problem was mapped into an ordinal potential game model, and a distributed strategy adjustment algorithm for nodes was designed accordingly. The strategy vector resulting from the algorithm converges to the Nash equilibrium; minor complexity and preferable approximate ratios can be represented by the algorithm as well. The performance of the algorithm was analyzed through simulation experiments which indicate a well-constructed topology. Every objective was upgraded when model parameters were set suitable.